Neolithic Rice Cultivation and Consequent Landscape Changes at the Baodun Site, Southwestern China - Zhang, Jianping; Lv, Ying; Yu, Lupeng; Tang, Miao; Huang, Ming; Shao, Konglan; Huan, Xiujia; Wen, Changhui; Dong, Yajie; Jiang, Ming; He, Kunyu; Yan, Xue; et al. (Frontiers in Earth Science, 2021)
Identifying when agricultural expansion has occurred and how it altered the landscape is critical for understanding human social survival strategies as well as current ecological diversity. In the present study, phytolith records of three profiles from the Baodun site area were dated to the period from 7500 to 2500 BP by optically stimulated luminescence and 14C dating, providing the first evidence that the Asian cultivated rice (Oryza sativa) progenitor was distributed in the Chengdu Plain as early as 7500 years BP. The percentage of rice bulliform with ≥9 scales and the concentration of rice phytoliths sharply increased by approximately 4200 aBP, suggesting that rice cultivation occupied a dominant position in survival strategy no later than approximately 4200 aBP, which might be driven by climate deterioration in eastern China. The results further showed that the proportion of Bambusoideae phytoliths increased synchronously with the increase in the proportion of rice phytoliths, suggesting that the vegetation structure near the site was changed intentionally as a consequence of increasing rice agricultural activity since 4200 aBP. The present study contributes to a deeper understanding of the distribution of wild rice and rice farming throughout the Baodun culture in the Chengdu Plain, and it also provides a glimpse of how humans intentionally changed the vegetation landscape on a local scale.